FAKTOR-FAKTOR YANG MEMENGARUHI CASH HOLDING PERUSAHAAN CONSUMER GOODS INDUSTRY - Ezelle Halim, Rosmita Rosyid (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to examine the effect of profitability, firm size, capital expenditure, net working capital, leverage, cash conversion cycle on cash holding in manufacture companies subsector consumer goods industry. The population of this study are all manufacture companies subsector consumer goods industry that is listed in Indonesia Stock Exchange (IDX) for the period of 2016 – 2018. The samples used in this research are 27 companies using purposive sampling method. According to likelihood test and hausman test used in Eviews 10.0 software, this model used random effect model. The result of this research is that profitability, leverage, and net working capital had positive effect on cash holding, while firm size, capital expenditure, and cash conversion cycle had no effect on cash holding.